FUNCTIONS OF ELECTRONIC LEARNING RESOURCES IN THE PROCESS OF PROFESSION-ORIENTED ORAL SPEECH TRAINING OF FUTURE TEACHERS OF FRENCH LANGUAGE (Journal of Information Technologies in Education (ITE), 2015)
The article analyzes the use of information and communication technologies in the formation of profession-oriented competence in listening and speaking (monologic, dialogic speech) of future teachers of French language in the initial school (I and II years). In order to assure the effective use of ICT in the formation of profession-oriented oral speech competence of future teachers of French language in terms of analyzing, systematizing and summarizing of scientific references the following criterion of the selection of electronic resources as the educational material were identified by the author: relevance (modernity); originality; thoroughness; topicality;informative value; applicability; availability; suitability to communicative needs of future teachers of French language, to their intelligence level and interests; professionally informative significancy;interactivity; contextuality; media intension; social and cultural value; educational value. In turn,the functional use of ICT in formation of profession-oriented oral speech competence of future teachers of French language is represented by the classification, according to which all electronic resources according to their functions are divided into communicative, share, documentation,generative and interactive that is demonstrated by the corresponding examples.
Keywords: information and communication technologies; profession-oriented; competence; oral speech; future teachers; French language